Persepsi Guru tentang Kepemimpinan Transformasional Kepala Sekolah di Smk Negeri 2 Bukittinggi - Ega Zulanda; Ermita Ermita (Journal of Educational Administration and Leadership, 2022)
This study aims to determine teachers' perceptions of the principal's transformational leadership at SMK Negeri 2 Bukittinggi as seen from, (1) Idealized Influence, (2) Inspirational Motivation, (3) Intellectual Stimulation. , and (4) individualized consideration. This type of research is descriptive research with quantitative research methods. The population of this research is teachers of SMK Negeri 2 Bukittinggi with as many as 100 teachers. The sample is 52 teachers using the Stratified Proportional Random Sampling technique. The instrument used is a Likert Scale model questionnaire. The results of data analysis and processing show that teachers' perceptions of the transformational leadership of school principals at SMK Negeri 2 Bukittinggi can be seen from the following explanations: (1) the idealized influence of principals at SMK Negeri 2 Bukittinggi is quite implemented with an average of 3.5 , (2) the inspirational motivation (Inspirational Motivation) of the principal at SMK Negeri 2 Bukittinggi has been carried out well with an average of 3.6, (3) the intellectual stimulation (Intellectual Stimulation) of the principal at SMK Negeri 2 Bukittinggi is quite carried out with an average an average of 3.4, (4) individualized consideration of principals at SMK Negeri 2 Bukittinggi has been carried out well with an average of 3.7. Overall, it was concluded that the teacher's perception of the transformational leadership of the head of SMK Negeri 2 Bukittinggi has been implemented well with an average of 3.6 (good).